Enhancing the efficiency and functionality of xylanase from Bacillus sp. RTS11: Optimization, purification, characterization, and prospects in kraft pulp bleaching: Optimizing Bacillus RTS11 xylanase for improved kraft pulp bleaching - Sahnoun, Sara; Yahiaoui, Bilal; Benlounissi, Aicha; Mouffok, Abdenacer; Ernst, Barbara; Alam, Manawwer; Houali, Karim; Benguerba, Yacine (Cellular and Molecular Biology, 2024)
Bacillus sp. RTS11, a xylanolytic strain, was isolated from the Algerian desert rocks. Genetic analysis revealed a remarkable 98.69% similarity to Bacillus pumilus. We harnessed optimization techniques, including Plackett-Burman screening and Box-Behnken optimization design, to amplify xylanase production and activity. The outcome of these efforts was an optimized medium that yielded an impressive xylanase production titer of 448.89 U, a threefold increase compared to the non-optimized medium (146 U). The Purification of xylanase was achieved through the three-phase partitioning technique, employing t-butanol and various chromatographic methods. Notably, anion exchange chromatography led to isolating a highly pure enzyme with a molecular weight of 60 kDa. The xylanase exhibited its peak activity at a temperature of 60°C and a pH of 9.0. When applied to pulp pretreatment, 20 U/g of xylanase demonstrated a substantial increase in the release of phenolic and chromophore compounds while reducing sugar content in the pulp. Furthermore, this versatile xylanase shows its ability to efficiently hydrolyze a variety of agro-industrial residues, including wheat bran, corn and grape waste, wheat straw, and sugarcane bagasse. These findings underscore the significant potential of this xylanase enzyme in biobleaching processes and the utilization of agro-industrial waste, opening up exciting avenues for sustainable and environmentally friendly industrial applications.